2005
DOI: 10.1111/j.1365-2656.2005.00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Flood initiates bottom‐up cascades in a tri‐trophic system: host plant regrowth increases densities of a leaf beetle and its predators

Abstract: Summary 1.Following the passing of a typhoon over central Japan in late August 2001, a largescale flood occurred owing to the heavy precipitation. Willow trees on the banks of the Yasu River were badly damaged. In the following year, we examined the effects of the flood on the regrowth response of a willow, Salix eriocarpa (Franch), and its subsequent effects on the densities of a leaf beetle, Plagiodera versicolora (Laicharting), and its predators. 2. We used 10 randomly selected pairs of heavily and lightly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 40 publications
4
52
0
Order By: Relevance
“…poor plant quality decreases herbivore population density as well as natural enemy performance and good plant quality enhances herbivore abundance as well as natural enemy performance (Hunter and Price 1992;Nakamura et al 2005;Kagata and Ohgushi 2006). For example, Nakamura et al (2005) showed that increased foliage sprouting after a flood increased the abundance of leaf beetles and their natural enemies. It has also been shown that 'bottom-up' cascades can be triggered by allelochemical compounds of plants, but here the cascading effects on natural enemies are reported to be weak or absent (Kagata and Ohgushi 2006; but see Soler et al 2005;Ode 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…poor plant quality decreases herbivore population density as well as natural enemy performance and good plant quality enhances herbivore abundance as well as natural enemy performance (Hunter and Price 1992;Nakamura et al 2005;Kagata and Ohgushi 2006). For example, Nakamura et al (2005) showed that increased foliage sprouting after a flood increased the abundance of leaf beetles and their natural enemies. It has also been shown that 'bottom-up' cascades can be triggered by allelochemical compounds of plants, but here the cascading effects on natural enemies are reported to be weak or absent (Kagata and Ohgushi 2006; but see Soler et al 2005;Ode 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to 'top-down' cascades, most studies on 'bottom-up' cascades show directional responses that are the same for herbivores and their natural enemies, i.e. poor plant quality decreases herbivore population density as well as natural enemy performance and good plant quality enhances herbivore abundance as well as natural enemy performance (Hunter and Price 1992;Nakamura et al 2005;Kagata and Ohgushi 2006). For example, Nakamura et al (2005) showed that increased foliage sprouting after a flood increased the abundance of leaf beetles and their natural enemies.…”
Section: Introductionmentioning
confidence: 99%
“…eriocarpa trees produce many new shoots during spring time. In addition, several abiotic stress (e.g., strong wind and flood) and biotic stress (e.g., gall initiation by gall midges) induce the vigorous production of new shoots near the damaged sites (Nakamura et al 2003(Nakamura et al , 2005. Our data suggest that P. versicolora adults use shoot odors as cue to found their suitable food resources.…”
Section: Discussionmentioning
confidence: 74%
“…This is probably because higher proportions of stripped trunk circumference result in greater inhibition of plant hormone transport. Since flooding often knocks down Salix trees and partly removes their branches above the ground (Nakamura et al 2005), the majority of Salix trees are well adapted to the physical damage of floods. One such adaptation may be a rapid regrowth response following disturbance that enables Salix trees to compensate for lost tissues.…”
Section: Discussionmentioning
confidence: 99%